2019
DOI: 10.1080/02656736.2019.1684575
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of CT-guided percutaneous thermal ablation for hepatocellular carcinoma adjacent to the second porta hepatis

Abstract: Purpose: This study assessed the efficacy and safety of computed tomography (CT)-guided percutaneous thermal ablation for hepatocellular carcinoma adjacent to the second porta hepatis. Methods: From January 2011 to June 2018, 59 consecutive patients (51 men and 8 women aged 29-85 years) with 65 tumors (mean maximum tumor diameter: 20.5 ± 1.2 mm; range: 5-50 cm) adjacent to the second porta hepatis underwent percutaneous CT-guided thermal ablation. The complete ablation rate, local progression-free survival (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…If residual tumor tissue was still present, additional RFA procedures were immediately performed to achieve complete ablation in one procedure [20]. A minimal ablative margin > 0.5 cm beyond the tumor in all directions or/and absence of arterial contrast enhancement and portal venous washout within the ablation zone suggestive of residual tumor one month after ablation was/were considered as complete ablation [25,26,29,30]. Patients were followedup every 3 months in the first year after RFA and every six months in the subsequent years until tumor recurrence or death.…”
Section: Follow-upmentioning
confidence: 99%
“…If residual tumor tissue was still present, additional RFA procedures were immediately performed to achieve complete ablation in one procedure [20]. A minimal ablative margin > 0.5 cm beyond the tumor in all directions or/and absence of arterial contrast enhancement and portal venous washout within the ablation zone suggestive of residual tumor one month after ablation was/were considered as complete ablation [25,26,29,30]. Patients were followedup every 3 months in the first year after RFA and every six months in the subsequent years until tumor recurrence or death.…”
Section: Follow-upmentioning
confidence: 99%
“…With the development of instruments and therapeutic schemes, MWA is increasingly used in many medical institutions worldwide to treat small and large HCCs and other solid tumors (12)(13)(14). In China, US is the most common image guidance tool for ablation, followed by CT.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] A study investigating the safety of MWA lesions near porta hepatis among 65 patients found that CT-guided MWA is an effective and safe treatment for tumors adjacent to the porta hepatis, particularly for lesions <3 cm. [ 25 ]…”
Section: Mwa Of Liver Lesions Near Portal Veinmentioning
confidence: 99%